Effect of vasopressin V1b receptor antagonist, SSR149415, on anxiety-like behavior and lewis lung carcinoma metastasis in mice - Amikishieva, A.V.; Ilnitskaya, S.I.; Nikolin, V.P.; Popova, N.A. (Experimental Oncology, 2011)
Aim: To study the effect of new vasopressin V1b receptor antagonist, SSR149415, on anxiety-like behavior and Lewis lung carcinoma metastasis in the anxious adult male mice of C57Bl/6J strain. This type of receptors was thought to act as potential targets mediating the effect of negative psychoemotional state on tumor progression. Methods: Anxiety-like psychoemotional state of the animals was produced using chronic social conflict model. Used behavioral tests were elevated plus-maze, social interaction test and open field test. Tumor cells were administrated on background of double or sixfold SSR149415 injections and the number of metastases in the lung were calculated 17 days later. Results: SSR149415 reduced the anxiety-like behavior measured in the elevated plus-maze and social interaction tests and did not affect locomotor activity in the open field test. Double and sixfold administration of the compound to such mice before and after inoculation of the tumor cells produced no effect on the metastasis rate. Conclusion: vasopressin V1b receptor is involved in the mediation of anxious behavior of animals but is not involved in the mechanism underlying the influence of negative psychoemotional state on Lewis lung carcinoma metastasis.